2015
DOI: 10.1037/apl0000020
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the black–white gap in cognitive test scores: Toward a theory of adverse impact.

Abstract: In understanding the causes of adverse impact, a key parameter is the Black-White difference in cognitive test scores. To advance theory on why Black-White cognitive ability/knowledge test score gaps exist, and on how these gaps develop over time, the current article proposes an inductive explanatory model derived from past empirical findings. According to this theoretical model, Black-White group mean differences in cognitive test scores arise from the following racially disparate conditions: family income, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 168 publications
(310 reference statements)
1
28
0
Order By: Relevance
“…Although tests of GMA are highly predictive of training and job performance (Berry, Poortinga et al, ; Bertua et al, ; Hülsheger et al, ; Hunter, ; Hunter & Hunter, ; Salgado & Anderson, ; Salgado et al, ), considerable evidence supports their adverse impact against ethnic groups (Hartigan & Wigdor, ; Hough & Oswald, ; Outtz & Newman, ; Roth et al, ). Despite this evidence, few studies have explored the underlying reasons for this impact beyond race/ethnicity itself which has limited theory development (exceptions are Cottrell et al, as well as Outtz and Newman, ). Developing theory about group differences has been further constrained by confounding variables as race/ethnicity is highly related to societal and socio‐cultural variables.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although tests of GMA are highly predictive of training and job performance (Berry, Poortinga et al, ; Bertua et al, ; Hülsheger et al, ; Hunter, ; Hunter & Hunter, ; Salgado & Anderson, ; Salgado et al, ), considerable evidence supports their adverse impact against ethnic groups (Hartigan & Wigdor, ; Hough & Oswald, ; Outtz & Newman, ; Roth et al, ). Despite this evidence, few studies have explored the underlying reasons for this impact beyond race/ethnicity itself which has limited theory development (exceptions are Cottrell et al, as well as Outtz and Newman, ). Developing theory about group differences has been further constrained by confounding variables as race/ethnicity is highly related to societal and socio‐cultural variables.…”
Section: Discussionmentioning
confidence: 99%
“…Generational status incorporated a range of factors including social class, gender, education, socioeconomic status, age, and language. In addition, as income (Cottrell, Newman, & Roisman, ) and nutrition (Benton & Roberts, ; Bleichrodt & Born, ; and Wachs et al, ) may improve for immigrants in their new country, these can contribute to increases in their GMA over time. Within these factors, two are consistently evidenced as demonstrating the largest impact on GMA test score gaps between non‐immigrants and immigrants: education and language fluency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study uses several frameworks and concepts about how early experiences of infant/toddler Black boys are linked to their later outcomes. They include the bio-ecological framework (Bronfenbrenner & Morris, 2007), the integrative model for the study of developmental competencies in minority children (García Coll et al, 1996), and the concepts of toxic stress (Shonkoff et al, 2012) and adverse impact (Cottrell, Newman, & Roisman, 2015).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Research has identified several factors that account for these GMA test score differences, such as educational quality for students (Rindermann & Thompson, ) and language skills for adults (de Meijer et al, ; te Nijenhuis & van der Flier, ). Other factors that may improve after immigration and contribute to GMA include income (Cottrell, Newman, & Roisman, ) and nutrition (Benton & Roberts, ; Bleichrodt & Born, ; Wachs et al, ). Despite the potential for improvements for immigrants in their new country, the impact of these factors on GMA will take time and are likely contingent on employment and economic success.…”
Section: Introductionmentioning
confidence: 99%